Uporaba epifitskih lišajev kot kazalnikov kakovosti zraka ob izbranih testnih odsekih cest v Sloveniji - Poličnik, Helena (Acta silvae et ligni, 2013)
For the assessment of air quality at locations along selected road sections with different traffic density, epiphytic lichens were used as passive reactive bioindicators. With the mapping at different distances from the roadside at each location, the trafficrelated pollution impact area was assessed. Two different mapping methods were used, specifically the simple assessment of air quality, based on the assessment of frequency and coverage of different lichen growth forms (the SI method), and more demanding one, based on mapping of lichen species (the VDI method). We conclude that at locations with moderate traffic density (average daily traffic < 20,000) the traffic-related emissions have an influence on air quality as well, except that the impact is limited to a narrow zone along the roads (< 100 m). The epiphytic lichen species composition, the number of different lichen species, as well as calculated indexes of air purity according to two different methods indicate influence of traffic-pollution in the first mapping zone (adjacent to roads), with the impact level decreasing with the distance from the roads.
Keywords: lišaji; promet; popisi lišajev; bioindikatorji; Slovenia; Slovenija